Elaboration and validation of a Homophobia Scale in secondary students at an emblematic national school in Perú - LOZADA, ORIANA RIVERA; ZAMALLOA LEGONÍA, EMILIO RAÚL; CRISTINA, ISABEL (International Journal of Psychosocial Rehabilitation, 2020)
In Peru, homophobia is not a widely addressed topic and thus, there do not exist psychometric tests to measure this variable. This is why this research was born with this objective: to build and identify the validity and reliability of a homophobia scale in secondary students at an emblematic national school in Rímac. Hence, we elaborated pertinent items, which were evaluated through expert judgement and proved that the items had an adequate content validity. In addition, the test’s items achieved adequate homogeneity and communality indexes. In order to determine construct validity, we undertook an exploratory factor analysis where we obtained an underlying three-factor structure as a result which explains the variance (50.757%). Moreover, we determined reliability through the split-half method, Cronbach’s Alpha and McDonald’s Omega, which gave us indexes higher than 0.70. Finally, we obtained a Likert-type scale with 18 items divided into 2 dimensions: Personal Homophobia and Interpersonal Homophobia with adequate evaluation scales differentiated according to gender.